Strategic Choice of the Subsidiaries:: Contextual and Operational Factors - Couto, João; da Conceição, Vitor; Amaral Fortuna, Mário (Journal of Comparative International Management)

(untitled) (Management Futures, 2003)
Considering the subsidiaries of multinational companies, a study of the conditions affecting the strategic choice is conducted. Beginning with an analysis of the taxonomies of subsidiaries, two strategic models were selected to test three hypotheses: one, regarding the variables that influence the strategic choice; a second, about the relationship between the two classification models and a third, about the influence of the type of subsidiary on performance. This study involved five European countries, namely the United Kingdom, France, Germany, Sweden and Portugal. It concludes that nation based variables have important influence in the determination of subsidiary strategic roles. This influence is present especially in terms of national culture with variables like individualism and uncertainty avoidance, while analyzing relationships, and age and technological capacity, while analyzing functions. We also found that both models used are independent, suggesting that they are complementary models and not substitutes.